Improving Information Systems Students' Presentation Soft Skills Through Lesson Plan Study - Maimun, Maimun; Ahmad, Adi; Maulana, Riyan; Yonoriadi, Yonoriadi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Presentation skills are essential soft skills that Information Systems students must master to meet both academic and professional demands. This study aims to enhance students’ presentation skills through the implementation of lesson plan study as a collaborative learning approach. A mixed-methods design with a quasi-experimental pre-test and post-test control group was employed. The participants were 20 Information Systems students at STMIK Indonesia Banda Aceh. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using statistical tests (t-test/ANOVA) as well as thematic analysis. The findings reveal a significant improvement in students’ presentation skills after participating in the lesson plan study, particularly in terms of self-confidence, communication clarity, and adaptability in diverse presentation contexts. The approach also fostered collaboration, constructive feedback, and self-reflection. Therefore, lesson plan study can be considered an effective strategy to improve presentation soft skills among Information Systems students, while also preparing them for future professional challenges.